2022
DOI: 10.1039/d2py00302c
|View full text |Cite
|
Sign up to set email alerts
|

New fluorescence labeling isotactic polypropylenes as a tracer: a proof of concept

Abstract: Propylene-co-N-pentenyl-carbazole copolymers P(P-co-PK)s containing a low amount of isolated PK units were prepared by using the isospecific homogeneous Ziegler-Natta (Z-N) catalytic system rac-dimethylsilylbis(1-indenyl)zirconium dichloride / methylaluminoxane (MAO) with the aim...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Fluorescence staining has been previously pursued as a strategy for plastics detection. Primarily, it has been used as a detection tool for identifying plastic materials among a variety of substances in single waste streams , or particles (i.e., micro- and nano-plastics) within natural samples. One of the prominent fluorophores used is Nile red, which is arguably the most used in the microplastic community to detect and quantify microplastic particles. Yet, many of these fluorescent studies only collect bulk fluorescence signals at a specific emission wavelength and largely ignore important spectral information from the stain adsorbed onto plastic. Herein, we present a new analysis method of Nile red fluorescence that enables us to quantify plastic aging, which overcomes the limitations of more traditional techniques, like FTIR or contact angle.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence staining has been previously pursued as a strategy for plastics detection. Primarily, it has been used as a detection tool for identifying plastic materials among a variety of substances in single waste streams , or particles (i.e., micro- and nano-plastics) within natural samples. One of the prominent fluorophores used is Nile red, which is arguably the most used in the microplastic community to detect and quantify microplastic particles. Yet, many of these fluorescent studies only collect bulk fluorescence signals at a specific emission wavelength and largely ignore important spectral information from the stain adsorbed onto plastic. Herein, we present a new analysis method of Nile red fluorescence that enables us to quantify plastic aging, which overcomes the limitations of more traditional techniques, like FTIR or contact angle.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some of us reported the synthesis of new copolymers of propylene fluorescent comonomer N-pentenyl-carbazole (P(P-co-PK) contained in low amou Scheme 1) [24]. Such copolymer samples can be readily prepared by copolymeriz the two comonomers (N-pentenyl-carbazole and propylene) using Ziegler-Natt catalytic systems and they can show chemico-physical properties very similar to i polypropylene (i-PP) as well as the distinctive fluorescence of the carbazole gro also demonstrated that P(P-co-PK)/commercial i-PP homogeneous blend films con 1% by weight of P(P-co-PK) retain the same optical feature of P(P-co-PK).…”
Section: Introductionmentioning
confidence: 99%
“…Propylene-co-N-pentenyl-carbazole copolymer structure. Therefore, we suggested that P(P-co-PK) s , due to their high compatibility with i-PP and similar stability, can be used for the fluorescent tagging of i-PP allowing for its detection in the recycling processes of plastics [24]. Starting from these foregoing results, we hypothesized that this approach could be used to obtain fluorescent copolymers of other common plastic materials such as polyethylene (PE) and polystyrene (PS), thus making it suitable to be used for the fluorescent tagging of their homologous homopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Beside these approaches, copolymerization of the olefin with an olefin bearing the chromophore, i.e., carbazole as in the present study, is the most cost-effective method to access these materials. Most cases in literature deal with the synthesis of PE-based copolymers, and studies about the preparation of PP-based are quite rare. In the latter case, copolymers of PP with 9 H -alkenyl carbazole, in which the olefin and the photoactive group are linked by spacers of different length (3 and 9 carbons long), have been synthesized by using metallocene and postmetallocene catalysts. One of these research groups has investigated this kind of PP copolymers as fluorescent probes to track the effect of PP microplastics on organism in aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases in literature deal with the synthesis of PE-based copolymers, and studies about the preparation of PP-based are quite rare. In the latter case, copolymers of PP with 9 H -alkenyl carbazole, in which the olefin and the photoactive group are linked by spacers of different length (3 and 9 carbons long), have been synthesized by using metallocene and postmetallocene catalysts. One of these research groups has investigated this kind of PP copolymers as fluorescent probes to track the effect of PP microplastics on organism in aquatic environments. The other group , has carried out a thorough study on the properties of poly­(propylene- co -11-carbazole-1-undecene) (PK), showing that thermal and mechanical performance of those materials are better than those of PP, when irradiated with UV light.…”
Section: Introductionmentioning
confidence: 99%